PENINGKATAN KEPEDULIAN SOSIAL SISWA MELALUI PENGUATAN NILAI KARAKTER BERBASIS PBL PADA MATERI PERLAWANAN BANGSA INDONESIA DALAM PEMBELAJARAN IPS KELAS VI SD (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study arises from the observation that the affective aspect in elementary Social Studies (IPS) learning, especially students’ social awareness, has not been optimally developed because teaching practices still focus more on cognitive outcomes and less on the internalization of social values. The purpose of this research is to examine how students’ social awareness can be improved through strengthening character values using a Problem Based Learning (PBL) approach, particularly in the topic of Indonesian national resistance for sixth-grade students. The study uses a Systematic Literature Review (SLR) method guided by the PRISMA framework, which involves stages of identification, screening, eligibility, and inclusion. Data were obtained by searching for relevant scientific articles on Google Scholar, from which 15 articles were selected based on predetermined criteria for further analysis. The results show that the use of the PBL model is effective in increasing students’ social awareness, mainly through activities such as problem solving, group discussions, and reflection. In addition, embedding character values within the material on national resistance helps build students’ empathy, teamwork, and responsibility. Overall, the application of PBL in Social Studies learning is effective in supporting the development of both cognitive skills and affective qualities in students.